Current techniques for lymphatic imaging: State of the art and future perspectives - Xiong, Lingyun; Engel, Holger; Gazyakan, Emre; Wähmann, Melodie; Hünerbein, Michael; Sun, J.; Kneser, Ulrich; Hirche, Christoph (European journal of surgical oncology, 2014)
Techniques for lymphatic imaging are aiming at accurate, simple and minimal-invasive approaches with less side-effects and repetitive application. Limitations are emerging in conventional techniques, and new techniques have shown their advantages in high resolution and sensitivity as well as transcutaneous imaging. In the present review, these techniques and their applications are reviewed and elucidated, aiming at a better understanding of recent advancements and current trends of lymphatic imaging as well as promising techniques for future research.
Online 14 December 2013
Gesehen am 21.09.2020